Manipulating the Crystalline Morphology in the Nonfullerene Acceptor Mixture to Improve the Carrier Transport and Suppress the Energetic Disorder. Issue 2 (5th November 2021) - Zhang, Ming; Zhu, Lei; Qiu, Chaoqun; Hao, Tianyu; Jiang, Yufeng; Leng, Shifeng; Chen, Jiajun; Zhou, Guanqing; Zhou, Zichun; Zou, Yecheng; Su, Xuan; Shi, Zhiwen; et al.
Abstract : Mixtures of nonfullerene acceptors (NFAs) are prepared to fine‐tune bulk heterojunction (BHJ) thin‐film morphologies. The acceptor phase resulting from these mixtures has unique physical properties with excellent optoelectronic processes that dictate the output of organic photovoltaic (OPV) devices. Remarkable short‐circuit current densities ( J SC ) and fill factors (FFs) are achieved due to the formation of better crystalline fibrils that suppress geminate recombination, leading to improved charge transport with enhanced crystallinity and aligned cascading energy levels confirm efficient exciton diffusion and dissociation, yielding more effective exciton recycling. The decreased Urbach energy and suppressed energetic disorder account for the improvement in the open‐circuit voltage ( V OC ). A maximum power conversion efficiency of 17.86% is obtained, underscoring the importance of using specific material interactions to produce a suitable morphology and manage energy loss, resulting in ideal organic solar cell (OSC) devices. Abstract : Ternary organic solar cells are fabricated, achieving a significant power conversion efficiency (PCE) improvement, by virtue of an optimized crystalline feature. The optimal morphology ensures efficient exciton diffusion and dissociation, increases the charge transport with reduced recombination, and suppresses energetic disorder, yielding a high efficiency of 17.86%.